Antimicrobial peptide based magnetic recognition elements and Au@Ag-GO SERS tags with stable internal standards: a three in one biosensor for isolation, discrimination and killing of multiple bacteria in whole blood. Issue 47 (15th November 2018) - Yuan, Kaisong; Mei, Qingsong; Guo, Xinjie; Xu, Youwei; Yang, Danting; Sánchez, Beatriz Jurado; Sheng, Bingbing; Liu, Chusheng; Hu, Ziwei; Yu, Guangchao; Ma, Hongming; Gao, Hao; et al.
Abstract : A SERS based biosensor has been developed for isolation, detection and killing of multiple bacterial pathogens. Abstract : In this study, a new biosensor based on a sandwich structure has been developed for the isolation and detection of multiple bacterial pathogens via magnetic separation and SERS tags. This novel assay relies on antimicrobial peptide (AMP) functionalized magnetic nanoparticles as "capturing" probes for bacteria isolation and gold coated silver decorated graphene oxide (Au@Ag-GO) nanocomposites modified with 4-mercaptophenylboronic acid (4-MPBA) as SERS tags. When different kinds of bacterial pathogens are combined with the SERS tags, the "fingerprints" of 4-MPBA show corresponding changes due to the recognition interaction between 4-MPBA and different kinds of bacterial cell wall. Compared with the label-free SERS detection of bacteria, 4-MPBA here can be used as an internal standard (IS) to correct the SERS intensities with high reproducibility, as well as a Raman signal reporter to enhance the sensitivity and amplify the differences among the bacterial "fingerprints". Thus, three bacterial pathogens ( Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa ) were successfully isolated and detected, with the lowest concentration for each of the strains detected at just 10 1 colony forming units per mL (CFU mL −1 ). According to the changes in the "fingerprints" of 4-MPBA, three bacterial strains were successfully discriminated using discriminant analysis (DA). In addition, the AMP modified Fe3 O4 NPs feature high antibacterial activities, and can act as antibacterial agents with low cellular toxicology in the long-term storage of blood for future safe blood transfusion applications. More importantly, this novel method can be applied in the detection of bacteria from clinical patients who are infected with bacteria. In the validation analysis, 97.3% of the real blood samples (39 patients) could be classified effectively (only one patient infected with E. coli was misclassified). The multifunctional biosensor presented here allows for the simultaneous isolation, discrimination and killing of bacteria, suggesting its high potential for clinical diagnosis and safe blood transfusions.